2017
DOI: 10.1016/j.schres.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits predicting quality of life and overall functioning in schizophrenia

Abstract: Introduction Clinical symptoms and sociodemographic variables predict level of functioning and quality of life in patients with schizophrenia. However, few studies have examined the effect of personality traits on quality of life and overall functioning in schizophrenia. Personality traits are premorbid to illness and may predict the way patients experience schizophrenia. The aim of this study was to examine the individual and additive effects of two core personality traits—neuroticism and extraversion—on qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…Viewed as an individual resource, personality can positively or negatively influence QoL. In this study, we found that, for both patients and caregivers, neuroticism was clearly associated with lower (mental) QoL, as previously reported in various contexts (patients with cancer, patients with neurological diseases or problems, and patients with schizophrenia). Similar to the findings of previous studies, we found that extraversion may be related to higher mental QoL (for patients and caregivers) and lower physical QoL (for caregivers only).…”
Section: Discussionsupporting
confidence: 86%
“…Viewed as an individual resource, personality can positively or negatively influence QoL. In this study, we found that, for both patients and caregivers, neuroticism was clearly associated with lower (mental) QoL, as previously reported in various contexts (patients with cancer, patients with neurological diseases or problems, and patients with schizophrenia). Similar to the findings of previous studies, we found that extraversion may be related to higher mental QoL (for patients and caregivers) and lower physical QoL (for caregivers only).…”
Section: Discussionsupporting
confidence: 86%
“…The proposed model in this study is consistent with the models presented in other studies (4,18,31,33). The direct effect of neuroticism on quality of life was greater than the indirect effect of this variable, which is consistent with previous research (8,34). In fact, neuroticism can increase an individuals' readiness to experience stressor events and make them prone to experience negative emotions and frustration (35).…”
Section: Discussionsupporting
confidence: 91%
“…It could be useful in applications for career development and counseling in the human resources or academic areas [30,31], adaptive e-learning systems [32], diagnosis of mental health disorders (borderline personality disorder [33], depression [3], schizophrenia [34], eating disorder [35] or sleep disorders [36]), virtual psychologist applications [37], and personalized health assistance [38]. It was also shown that there are links between common physical diseases (such as heart attacks, diabetes, cancer, strokes, arthritis, hypertension, and respiratory disease) and Big Five personality traits [39] such that these diseases influence the age-related personality accelerating with 2.5 years decrease for extraversion, 5 years decrease for conscientiousness, 1.6 years decrease for openness, and 1.9 years increase for emotional stability.…”
Section: Introductionmentioning
confidence: 99%